Correlation between fruit consumption and 10-year all-cause mortality in patients with dyslipidemia - Zheng, Yuanjuan; Sun, Feifei; Ye, Suling; Zhu, Jinzhou; Ma, Yu; Shan, Mengmeng; Li, Shaomi; Chen, Yingying; Li, Jie (Frontiers in Nutrition, 2024)
Background: Consuming fruit provides health benefits. Reportedly, increased fruit consumption reduces the risks of hypertension and cardiovascular disease. However, existing studies have not clarified the effect of fruit consumption on mortality risk in patients with dyslipidemia. This study aimed to assess the correlation between the consumption of different types of fruits and all-cause mortality in patients with dyslipidemia. Methods: A total of 2,184 patients with dyslipidemia were included in this study, and trends in the correlation between the frequency of consumption of different types of fruits and the 10-year all-cause mortality risk in patients with dyslipidemia were analyzed by smoothed curve fitting, Cox regression, and Kaplan–Meier curve analysis. Subgroup analysis and interaction test were applied to analyze the stability of the effect of apple consumption on 10-year all-cause mortality in patients with dyslipidemia. Results: Smoothed curve fitting and Cox regression analyses revealed a significant reduction in the 10-year all-cause mortality risk in patients with dyslipidemia who consumed apples 3–4 times/week (hazard ratio [HR] = 0.61, 95% confidence interval [CI]: 0.43–0.87, P = 0.007) and in those who consumed bananas 3–4 times/week (HR = 0.71, 95% CI: 0.52–0.98, P = 0.039), with a more pronounced effect in patients who consumed both apples and bananas (HR = 0.55, 95% CI: 0.30–0.99, P = 0.045). Other fruits did not exhibit similar effects. Conclusion: Consuming apples or bananas 3–4 times/week significantly improved the 10-year survival rate in patients with dyslipidemia, and the effect was even more profound in patients who consumed both fruits.